SPLIT PERSONALITY IN KEENEN IVORY WAYANS'S LITTLE MANMOVIE (2006): A PSYCHOANALYTIC APPROACH - ASMI, RENI INDRI (2011)
The major problem of the research on the movie Little Man is how split personality is described in Keenen Ivory Wayans. Meanwhile, this problem is limited on the major character Calvin Simmons viewed by psychoanalytic approach. The objectives of this study are to analyze the movie based on the structural elements and the personality of the major character based on psychoanalytic approach. The benefit of the study is to give additional information that can be used by the other literature researches who are interested in analyzing this movie. This study is a literary study, which can be categorized into a descriptive qualitative study. The object of this study is Little Man movie, a movie by Keenen Ivory Wayans. The data sources are primary and secondary data sources. The primary data sources is the movie itself, Litte Man movie, and the secondary data sources are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive qualitative analysis. Based on structural analysis, Little Man movie has a good quality that tells one's search for self identity may result in split personality. The characters, theme, setting, point of view, plot, casting, mise-en-scene, cinematography, editing and sound influence each other. The outcome of this study shows that the problem of major character causes the internal conflict of Calvin Simmons. Then, he separates his character into a little boy named little calvin. His ways is unnatural and irrational, finally, it causes him to do suicide.